Jewish Doctors’ Challenges in the Death Camps: Ethical Dilemmas? Choiceless Choices? The Human Condition? - Halpin, Ross (Conatus - Journal of Philosophy, 2019)
Most commentators have focused on ethical dilemmas and the idea that they were core to the actions of and decisions by Jewish doctors in SS concentration camps and ghettos during the Holocaust. While I recognize Jewish doctors did face ethical dilemmas, in this article, I shift my attention to include two other significant factors: choiceless choices, defined by the eminent Holocaust historian Lawrence Langer as “crucial decisions [that] did not reflect options between life and death, but between one form of abnormal response and another, both imposed by a situation that was in no way of the victim’s own choosing,” and the human condition, whereby decisions and actions were triggered by personal traits and past experiences in response to particular situations and circumstances. Inherent in all three factors is the tenaciousness of reality and how the abhorrent conditions, immorality, inhumanity and evilness cast a shadow over every moment of the Jewish doctor’s life. My thesis is that decision-making was not one-dimensional but multi-dimensional. For the Jewish doctor every incident became a source of dread and tragedy. They were often not trained to treat some diseases or perform surgery and lacked experience to work in such conditions and cope emotionally and psychologically. I will attempt to show that how a person responds to an ethical dilemma is based on his or her own experiences and reasoning, and how they reacted to sudden and inexplicable incidents that threatened life or impacted survival induced abnormal actions and decisions. As Jewish doctors they were driven to be healers, to be normal, but they were forced by circumstances to kill or become perpetrators, acting abnormally. Tragically the abnormal became the norm. The Jewish doctors were professionally trained and culturally socialized to continue their roles as doctors. Nevertheless, they were human and were driven by the innate will to live.